Análise da taxa de mortalidade de Alphitobius diaperinus (Panzer) exposto a fumo triturado apreendido pela receita federal brasileira - Moscardi, Samira Costa (2018)
Brazilian poultry industry is the agribusiness area that has stood out the most in the last decades, being one of the world's leading producers. The efficiency of this activity is due to the organization of the chain, quality, health, productive gains and technology of the facilities. These links made Brazil reach the top of the production ranking, being the largest exporter of beef and the second largest producer. In this way, the production optimization of the intensive breeding system, offers a favorable environment for the development of diseases and pests, mainly the Alphitobius diaperinus, responsible for great damages in the chain. The present study evaluated the mortality rate of Alphitobius diaperinus (Panzer) exposed to crushed smoke seized from the Brazilian Federal Revenue Service. The experiment contained two treatments, being a reality of smoke in the open environment and a fresco for the control of small pox, both exercises were performed five repetitions. The data were submitted to a normality analysis by the Shapiro-Wilk test. After the analyzed analyzes, the results were good, but were complete for the control of cascudinho larvae, with an average of 66%. With this objective, it is useful to use control for the welfare control, besides the possibility of correct choice of tobacco from the Brazilian Federal Revenue Service.